The Application of Arbuscular Mycorrhizal Fungi (AMF) and Compost to Improve the growth of Teak Seedlings (Tectona grandis Linn. f.) on Limestone Post-mining Soil - Retno Prayudyaningsih; Ramdana Sari (Jurnal Penelitian Kehutanan Wallacea, 2016)
The characteristics of limestone post-mining soil are low physical, chemical and biological soil fertility, which have adverse effect on plant growth. Arbuscular mycorrhizal fungi (AMF) and compost application is expected to enhance plant growth. AMF association expand nutrients absorption area. Compost application provides nutrients and increases soil porosity, which significantly supports plant growth and AMF development. Therefore, the effectiveness of AMF or compost could be improved if both are applied simultaneously. The study was conducted to determine the effectiveness of the AMF and compost to teak seedling growth on limestone postmining soil. A completely randomized design was applied with factorial pattern. There are 2 factors of treatment i.e AMF inoculation (K=without AMF, A=Acaulospora sp., G=Gigaspora sp., and M=Mix of Acaulospora sp. and Gigaspora sp.) and Compost percentage (K0=without compost, K5=5% compost, K10=10% compost, and K15=15% compost). The results showed AMF and compost application improved growth compared to the quality of teak seedling. Inoculation of Gigaspora sp. with 5% compost gave the best responses for stem diameter and seedling quality index. The best leaves accretion was denoted by the seedlings that were inoculated by Mix AMF with 5% compost. Inoculation of Acaulospora sp. with 15% compost had better growth response for biomass. Root-top ratio and AMF colonization were shown in seedling that was inoculated by Gigaspora sp. with 15% of compost. Gigaspora sp. with 5% compost, therefore, is the best combination for increasing seedling quality.